The Macroeconomic Consequences of the Savings and Loan Debacle - Manchester, Joyce; McKibbin, Warwick J. (The Review of Economics and Statistics, 1994)
This paper used a general equilibrium framework to examine the macroeconomic consequences of the recent failures and subsequent bailout in the savings and loan industry. We distinguish between the losses in the capital stock, the economic effects of alternative methods of funding those real losses, and the intertemporal transfer of real resources implicit in backing the financial assets used. We then embed the analysis in a general equilibrium, multi-country model with intertemporal budget constraints that allows for the interaction of intertemporal adjustment and expectation revisions. The more complete model is used to explore the consequences of the S&L debacle on the evolution of the U.S. economy during the 1980's and 1990s.